IDE MENGAKOMODASI CONSTITUTIONAL COMPLAIN SEBAGAI KEWENANGAN BARU MAHKAMAH KONSTITUSI INDONESIA - Bayu Lesmana Taruna (JURNAL LEGALITAS, 2010)
Constitutional Court\'s presence in the Indonesian state administration system in, order to reform state affairs which menutut law enforcement in a fair and democratic about the constitution. In general, society or justitiabellen who feel their human rights have been violated by the law expect to benefit by the existence of the Constitutional Court. Further development of the Constitutional Court has managed to provide protection for the constitutional rights of citizens from any violation of laws provisions. Nevertheless, the constitutional court has weaknesses. Constitutional Court only has the authority to test the validity of the laws against the Constitution, and not be able to test the implementation or application of the regulations. Therefore the Constitutional Court can not examine these cases a concrete constitutional authority the Court examined the constitutionality of a Konstiusi only legislation that abstract. The Constitutional Court does not have to check the cases involving violalions of constitutional rights of individuals through a mechanism known as a constitutional complaint. Keywords: Constitutional Court\'s, Constitutional Review, constitutional Complain